The Red Route to Open Access?: Scholarly Publishing and the Politics of National Identity in Post-Soviet Ukraine - Haigh, Maria; Haigh, Thomas (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Ukraine has adopted a distinctive approach to open access, in which the full text of all journals published in the country is added to a national repository. We analyze this initiative and its underlying legal mandate, placing them in cultural and historical context and comparing them with existing models of open access. L’Ukraine a adopté une approche distincte au libre-accès : les articles de tous les journaux du pays sont intégralement versés dans un dépôt national. Nous avons analysé cette initiative et ses implications juridiques dans un contexte culturel et historique et mis en comparaison à d’autres modèles de liber-accès.